China in the middle-income trap? - Linda Glawe; Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2017)
Over the last decade, a growing body of literature dealing with the phenom-enon of the "middle-income trap" (MIT) has emerged. The term MIT usually refers to countries that have experienced rapid growth and thus reached the status of a middle-income country (MIC) in a very short period of time, but have not been able to further catch up with the group of high-income economies. In particular, since the beginning growth slowdown of the Chinese economy in 2011, there has been rising concern that China is, or will also be, confronted with such a trap. This paper analyzes the Chinese MIT situation taking into account both the (absolute and relative) empirical MIT defi-nitions and MIT triggering factors identified in the literature. We not only survey the recent literature, but also make our own MIT forecasts and analyze under which condi-tions China could be caught in an MIT.
Keywords: O10; O40; O47; O53; 330; middle-income trap; China; economic growth; economic development; human capital; export structure; total factor productivity